PENGARUH DOSIS PUPUK KANDANG SAPI DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG UNGU (Solanum Melongena L.) - Prastya, Yona; Puspitorini, Palupi (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
This study aims 1) To determine the effect of the interaction types of cow manure with liquid organic fertilizer on the grwoth and yield of purple eggplant. 2) two know the effect of cow manure on the growth and yield of purple eggplant, 3) to know in the influence of liquid organic fertilizier on the growth and yield of purple eggplant . this research was conducted by using Randomizedby Block Design in Faktorial ( RAK ) with two factors, the first factor is Cow manure (K), consisting of three levels ie cow manure 500 gram (K1), cow manure 750 gram (K2), com manure 1000 gram (K3 ). The second factor is liquid organic fertilizer ( P ) consists of three levels : liquid organic fertilizer 3 mili ( P1 ) liquid organik fertilizer 6 mili (P2), liquid organik fertilizer 9 mili (P3). The observed variables in include plant height, number of leaves, number of fruits, fruit length and fruit weight . Data were analyzed using analysis of variance (ANOVA) level of 5%. The results showed that: there was no interaction between cow manure and liquid organic fertilizer on growth and yield of purplish eggplant. Treatment of cow manure 500 gram ( K1 ) effect on plant height 56 hst and cow manure 1000 gram (K3 ) have an effect on total fruit length. In the treatment of liquid organik fertilizer 6 mili ( P2 ) effect on plant height 28 hst and the treatment of liquid fertilizerr 9 mili (P3 ) have an effect to harvest length 1. There is no interaction between cow manure an liquid fertilizer to the growth and yield of eggplant purple.